Malaysian nurses’ knowledge and attitudes regarding BRCA genetic testing - Liu, Kien Ting; Wan Rosli, Wan Rosilawati; Yusuf, Azlina; Lean Keng, Soon (Belitung Nursing Journal, 2021)
Background: Breast cancer genetic (BRCA) testing for cancer susceptibility is an emerging technology in medicine. Objective: This study assessed the knowledge and attitude of nurses regarding BRCA genetic testing in a tertiary teaching hospital in Malaysia. Methods: A descriptive cross-sectional study was conducted among 150 nurses using a simple random sampling technique in a tertiary teaching hospital in northeast peninsular Malaysia. Data were collected using a self-administered questionnaire consisting of socio-demographic data, assessing nurses’ knowledge and attitude regarding BRCA genetic testing. Fisher exact test analysis was used to determine the association between socio-demographic characteristics with knowledge and attitude level. In addition, the overall knowledge and attitude were analysed using the sum score of each outcome based on Bloom’s cut-off point. Results: Of the 150 nurses, 66.7% had high knowledge level about BRCA genetic testing, and 58% were positive towards genetic testing. The participants’ mean age was 28.9 years (SD = 6.70). Years of working experience (p = 0.014) significantly influenced knowledge level on BRCA genetic testing, whereas speciality working experience (p <0.001) significantly influenced BRCA genetic testing attitudes. Conclusions: The results show that most nurses have adequate knowledge of BRCA genetic testing. However, their attitude could be termed negative. Therefore, targeted education programs on BRCA genetic testing and risk are needed to improve the knowledge and attitude of nurses and, ultimately, can educate the women and increase health-seeking behaviour among eligible women.